Generational Differences in Self-Esteem and Vocal Perception Among Brazilian Gay Men - Trevizani, Gabriel [UNESP]; Nascimento, Marcia Helena Cassago; Quinalha, Renan; Azevedo, Renata Rangel (Elsevier, 2025)
Introduction: Self-esteem and vocal perception are central aspects of identity and self-presentation, particularly within marginalized communities where voice and self-concept can be deeply intertwined with social acceptance and cultural dynamics. Among Brazilian gay men, generational differences in these areas may reflect broader social changes, shifts in stigma, and evolving notions of masculinity. This study aims to explore these differences, examining how self-esteem and self-assessed vocal descriptions vary across generations, thereby shedding light on specific needs and areas for potential support within these communities. Objectives: To compare self-esteem and self-assessed vocal descriptions among different generations of Brazilian gay men. Study Design: Observational, cross-sectional, mixed-methods study. Methods: A convenience sample of 266 Brazilian gay men completed an online survey, which included a sociodemographic questionnaire, the Rosenberg Self-Esteem Scale, and self-assessed vocal descriptive terms, between June 2 and July 14, 2023. Participants were categorized into generational groups based on age, following the definitions provided by the Pew Research Center: Baby Boomers (born 1946-1964), Generation X (born 1965-1980), Millennials (born 1981-1996), and Generation Z (born 1997-2012). Data analysis was performed using random forest techniques to identify variables relevant to generational differences and self-esteem, the frequency of descriptive terms, and multinomial logistic regression models to associate terms with self-esteem classification. Results: Participants ranged from 18 to 71 years old, with an average age of 33.6 years. Regarding generations, 1.9% were Baby Boomers, 13.2% were Generation X, 63.2% were Millennials, and 21.8% were Generation Z. The Baby Boomer and Generation X cohorts exhibited satisfactory self-esteem, while Millennials and Generation Z showed average self-esteem. Terms such as “low,” “good,” “out of tune,” and “effeminate” were significant for Generation X; “affected,” “pleasant,” “cheerful,” and “masculine” for Millennials; and “high-pitched,” “cheerful,” “excited,” “common,” “effeminate,” “insecure,” and “shy” for Generation Z. Conclusion: There were significant differences in self-esteem and vocal perception among the different generations of Brazilian gay men. Younger generations, particularly Millennials and Generation Z, demonstrated average levels of self-esteem, highlighting the need for targeted interventions to improve self-esteem and vocal perception within these groups.
Keywords: Personal satisfaction—Self-concept—Sexual and gender minorities—Voice